2019
DOI: 10.1080/15592294.2019.1615358
|View full text |Cite
|
Sign up to set email alerts
|

Fusaric acid-induced promoter methylation of DNA methyltransferases triggers DNA hypomethylation in human hepatocellular carcinoma (HepG2) cells

Abstract: Fusaric acid (FA), a mycotoxin contaminant of maize, displays toxicity in plants and animals; however, its epigenetic mechanism is unknown. DNA methylation, an epigenetic modification that regulates gene expression, is mediated by DNA methyltransferases (DNMTs; DNMT1, DNMT3A, and DNMT3B) and demethylases (MBD2). The expression of DNMTs and demethylases are regulated by promoter methylation, microRNAs (miR-29b) and post-translational modifications (ubiquitination). Alterations in these DNA methylation modifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Then, the immuno-precipitates were recovered by centrifugation (2,500 g , 4°C, 60 s), washed three times in RNA immunoprecipitation buffer, followed by re-suspension in Qiazol Reagent (500 µl). RNA was isolated from both the reference and m6A-precipitated samples, as previously described [ 24 ]. The expression of p75NTR in the m6A-precipitated sample was normalized against the expression of p75NTR in the reference sample in order to determine the ratio of m6A methylated p75NTR relative to the total p75NTR expressed [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, the immuno-precipitates were recovered by centrifugation (2,500 g , 4°C, 60 s), washed three times in RNA immunoprecipitation buffer, followed by re-suspension in Qiazol Reagent (500 µl). RNA was isolated from both the reference and m6A-precipitated samples, as previously described [ 24 ]. The expression of p75NTR in the m6A-precipitated sample was normalized against the expression of p75NTR in the reference sample in order to determine the ratio of m6A methylated p75NTR relative to the total p75NTR expressed [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The average methylation status of the above 15 CG pairs was notably exceeded in the peripheral CD4 + T cells in RA patients than that found in the health individuals (Figure 6C). It is well known that DNA methylation is regulated by DNA methyltransferases (DNMTs) (20,21). We then examined expression of DNMTs on CD4 + T cells and found that among DNMT1, DNMT3A, and DNMT3B, only DNMT1 mRNA expression was negatively correlated with the expression of Smad7 in CD4 + T cells (Figures 6D-F).…”
Section: Loss Of Smad7 Is Associated With Hypermethylation Of Smad7 P...mentioning
confidence: 95%
“…Some of the main food-borne mycotoxins—fusaric acid, fumonisin B 1 , deoxynivalenol, T-2 toxin, zearalenone, ochratoxin A, and aflatoxin B 1 ( Figure 4 )—have been shown to induce a change in the DNA methylation profile in human cell lines and animal models [ 213 , 214 , 215 , 216 , 217 , 218 , 219 ].…”
Section: Mycotoxinsmentioning
confidence: 99%
“…This study indicated that FA decreased 5-methylcytosine DNA content, which is indicative of global DNA hypomethylation in the HepG2 cell line. The decrease in global DNA methylation occurred as a result of the decrease in DNMT1, DNMT3A, and DNMT3B expression as well as an increase in MBD2 expression [ 213 ]. Furthermore, FA was shown to decrease DNMT1, DNMT3A, and DNMT3B expressions by inducing promoter hypermethylation of the DNMTs .…”
Section: Mycotoxinsmentioning
confidence: 99%
See 1 more Smart Citation